2019
DOI: 10.1021/acs.macromol.8b02480
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assemblies of Dendrimers Embedded in Networks of Lanthanide-Based Supramolecular Polyelectrolytes

Abstract: Supramolecular assemblies of dendrimers, with defined structures and tunable functionalities, are promising functional materials. Here we report a ternary system (lanthanide ion/bis-ligand/PAMAM dendrimer) capable of assembling in a cooperative way by forming a complex between anionic (metal–ligand) coordination polymers and the cationic PAMAM dendrimers. In off-stoichiometric mixtures, charge-stabilized spherical nanoparticles of ∼100 nm appear; they have either negative or positive surface charges depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…The PAMAM dendrimers contain both primary amine groups (pKa ≈ 10.5) at their surface and internal tertiary amines (pKa ≈ 6.5). [29,30] We conducted our experiments at pH = 6.5 (20 mM MES buffer) where the surface amine groups are supposed to be protonated completely. The internal tertiary amines may be partially protonated, but the exact protonation degree is difficult to determine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAMAM dendrimers contain both primary amine groups (pKa ≈ 10.5) at their surface and internal tertiary amines (pKa ≈ 6.5). [29,30] We conducted our experiments at pH = 6.5 (20 mM MES buffer) where the surface amine groups are supposed to be protonated completely. The internal tertiary amines may be partially protonated, but the exact protonation degree is difficult to determine.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have concluded that the compact molecular structure of dendrimers tends to create kinetically trapped PIC vesicles. [30,34,35] In other words, the dendrimer-based vesicles should be salt persistent. We checked this by adding salt to PAMAM/PSS-PEO-PSS vesicle dispersions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that PAMAM dendrimers might act as colloidal stabilizers and reducing agents in the synthesis of Au nanoparticles , . The enhanced colloidal stabilization has been associated with steric hindrance and electrostatic repulsion due to the coordination sphere network formed around the nanoparticles' surfaces , , .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by the selective change of the surface chemistry of PAMAM dendrimers, the colloidal stability of nanoparticles under variable chemical conditions can be improved. The characteristic surface chemistry along with well‐defined size of PAMAM dendrimers can also be further explored for the blending of more complex systems, which can deliver multifunctionality to the final material …”
Section: Introductionmentioning
confidence: 99%
“…22 Upon mixing with the cationic blocks, the local concentration of M-LEO in the assemblies increases hundreds of times, which dramatically shifts the equilibria of the coordination structures towards coordination polymers. 23,24 In this study, the Zn/LEO ratio is kept at 1/1, at which Zn-LEO can form linear coordination polymers, such that each coordination site carries a net charge of À2. For lanthanides (Ln), we fix the Ln/LEO ratio at 1/1.5, thereby producing 3D network structures such that each coordination unit carries 3 negative charges 26 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%